Human capital and long-run labor income risk - Luca Benzoni; Olena Chyruk (Federal Reserve Bank of Chicago, 2013)
This review article examines the role of labor income risk in determining the value of a person's human capital. We draw on the existing literature to present a model that incorporates various types of shocks to earnings. Within this framework, we highlight the implications of different assumptions about the correlation between market returns and labor income growth for the value of human capital and its riskiness. Further, the article surveys other work that applies similar ideas to assess the value and risk of pension promises. Finally, we discuss how to enrich the environment with heterogeneity in preferences and stock market exposures; endogenous labor supply and retirement decisions; health shocks; and human capital investment.
Keywords: G11; G12; 330; Human capital; life cycle; labor supply; retirement